Influence of different intervals for sweet corn processing on quantitative and qualitative characteristics - Richieri, Rodrigo da Silva (2021)
Sweet corn differs from common corn due to its lower concentrations of starch in relation to the sucrose in its endosperm, a characteristic that gives cultivars in this segment a unique sweet taste for this vegetable species. Because of this product’s high perishability, the interval between harvest and processing is recommended to be as short as possible so as to preserve both its quantitative and qualitative characteristics. The objective of this study was to observe the effects on the quantity and quality of sweet corn when it is harvested and subjected to late processing, i.e., periods that are not recommended. A randomized block design with five replications was adopted for the experiment. The following intervals were chosen for processing the ears of corn: 0, 4, 8, 12, 16, 20 and 24 hours after harvest. Characteristics such as the fresh weight of the ear with and without the husk, of only the cob, and of only the kernels from processing as well as the industrial yield were noted. The sample’s moisture, soluble solids content, titratable acidity, and sucrose and reducing sugar content were also evaluated. No quantitative gains or losses were verified during the postharvest storage and pre-processing periods for the ears of sweet corn. Depending on the interval before processing there was a 15.6% reduction in the concentration of soluble solids.